Efficacy and safety of surgical and chemoimmunotherapy combination treatment in patients with renal carcinoma and pulmonary metastases - Syryło, Tomasz; Żołnierek, Jakub; Szczylik, Cezary; Zieliński, Henryk; Bortnowski, Leszek; Bogdanowicz, Andrzej (Contemporary Oncology/Współczesna Onkologia, 2010)
Background: Renal cell carcinoma (RCC) amounts to 3% of solid tumours in adults. In about 30% of newly diagnosed RCC patients metastases are found, the majority of them in the lungs. The aim of the study is to assess remission of lung metastases of advanced renal cancer after nephrectomy and chemoimmunotherapy. Prior to systemic treatment all patients were subject to nephrectomy (without metastasectomy), and metastatic spread of the disease was documented by CT scan. The therapy was based on IL-2 s.c., IFN- s.c., and 5-FU i.v. Performance status was assessed according to the ECOG scale, and response of target lesions according to RECIST criteria. Results: ECOG score in 54 patients: 0 in 5 patients, 1 in 43, and 2 in 6. After chemoimmunotherapy, 5 complete responses (9%) and 12 partial responses (22%) were observed. An objective response was noted in 17 cases. Mean CR duration was 24 months (which significantly prolonged patients’ survival). ECOG PS: 0 – 0, 1 – 4 patients, 2 – 1 pa-tient. Mean PR duration was 12 months (usually progression of cancer). The regimen used showed only transient toxicity with good treatment tolerance by patients. Conclusions: 1. Combined nephrectomy and chemoimmunotherapy is an effective and safe treatment option in patients with renal cancer and pulmonary metastases. 2. As a result of the administered chemoimmunotherapy 5 CRs were achieved, which significantly prolonged patients’ survival. 3. Treatment of RCC patients should be carried out in specialised centres and should be interdisciplinary in nature.